Effect of the milling atmosphere on the microstructure and mechanical properties of a ODS Fe-14Cr model alloy - Auger, M; de Castro, V; Leguey, T; Lozano-Perez, S; Bagot, P; Moody, M; Roberts, S (Elsevier, 2016)
A systematic study has been undertaken to assess how the milling atmosphere, in the processing of an ODS steel with nominal composition Fe-14Cr-0.3Y2O3 (wt. %), will affect the microstructure and mechanical properties of the resultant alloys. Batches of the steel were manufactured by a powder metallurgy route incorporating mechanical alloying, hot isostatic pressing, forging and heat treatment. Hydrogen or helium atmospheres were used in the mechanical alloying, with all other processing parameters remaining identical. Transmission electron microscopy (TEM) and Atom Probe Tomography (APT) show that both milling atmospheres promote a homogeneous dispersion of Y-rich nanoparticles in the final alloys, being smaller when milling in H. Previously reported mechanical characterisation of these alloys shows better mechanical response at high temperature for the alloy milled in a H. This can be justified by the presence of smaller Y-rich nanoparticles together with the absence of bubbles, observed in the alloy milled in He.